TOPRAKLARDA TUZ VE BOR HAREKETİNİN SİMİLASYON MODELLEMESİ - Ayten Karaca; Satea M. Omar; Sonay Sözüdoğru (Pamukkale University Journal of Engineering Sciences, 1998)
A computer simulation leaching model was applied to a laboratory study of salt and boron leaching from fine and coarse texture soil. Leaching was performed by ponding of water with 5 cm head and by intermittent water application. Computer estimations on the transport of salt and boron in the both types of soil were compared with the measured changes in salt and boron concentrations during the leaching processes. The results indicated that the calculated values in EC and boron during the leaching process showed conformity particularly during the intermittent application. The boron reclamation needed four to five times more water than the salt reclamation.